2008
DOI: 10.1007/s00125-008-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid dehydrogenase type 1 regulates insulin and glucagon secretion in pancreatic islets

Abstract: Aims/hypothesis Exposure to excess glucocorticoid is associated with pancreatic beta cell damage and decreased glucose-stimulated insulin secretion (GSIS). Inactive glucocorticoids (cortisone, 11-dehydrocorticosterone) are converted to active cortisol and corticosterone by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), which requires NADPH as cofactor, which is generated by hexose-6-phosphate dehydrogenase (H6PDH). We investigated the localisation and activity of 11β-HSD1 within pancreatic islets, and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
5
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 45 publications
7
42
5
4
Order By: Relevance
“…In contrast, incubation of mouse pancreatic islets with dexamethasone (0.5-50 nM), corticosterone (50 nM) or 11-dehydrocorticosterone (50 nM) for 2 h reduced glucagon secretion induced by low glucose levels, effects that were reversed by a GR antagonist (Swali et al 2008). The inhibitory action of 11-dehydrocorticosterone was partially reversed by a selective 11b-HSD1 inhibitor.…”
Section: Acute Effects Of Gcs On A-cell Function and Glucagon Releasementioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, incubation of mouse pancreatic islets with dexamethasone (0.5-50 nM), corticosterone (50 nM) or 11-dehydrocorticosterone (50 nM) for 2 h reduced glucagon secretion induced by low glucose levels, effects that were reversed by a GR antagonist (Swali et al 2008). The inhibitory action of 11-dehydrocorticosterone was partially reversed by a selective 11b-HSD1 inhibitor.…”
Section: Acute Effects Of Gcs On A-cell Function and Glucagon Releasementioning
confidence: 91%
“…The inhibitory action of 11-dehydrocorticosterone was partially reversed by a selective 11b-HSD1 inhibitor. This fact, along with the co-localisation of this enzyme in human and rodent islet a-cells, indicates that this islet cell type serves an important local function in pancreatic GC metabolism (Swali et al 2008). This situation may be different in other species, for example in rats, where this enzyme is expressed in non-a-cells (Rafacho et al 2014).…”
Section: Acute Effects Of Gcs On A-cell Function and Glucagon Releasementioning
confidence: 99%
“…11 -HSD1 is expressed in pancreatic islets and its expression is higher in islets from obese rodents where inhibition with carbenoxolone or selective 11 -HSD1 inhibitors (Davani et al, 2000, Ortsater et al, 2005 alleviates the 11-M a n u s c r i p t 14 ketoglucocorticoid-mediated suppression of insulin secretion in these models. An intriguing new finding suggests that 11 -HSD1 is expressed most highly in the glucagon secreting alpha cells, where the authors suggested the effects on insulin secretion might occur through a paracrine modulation of insulin secretion by this hormone (Swali et al, 2008). Again more work is required to dissect the functional role of glucocorticoids and 11 -HSD1 in the endocrine pancreas.…”
Section: Other Important Sites Of 11 -Hsd1 Expressionmentioning
confidence: 99%
“…A 11-β-HSD-1 a hasnyálmirigy alfa-sejtjeiben direkt módon szabályozza a glükagonszekré-ciót. Az alfa-sejtek glükokortikoidelválasztása parakrin hatás, amely hatással lehet a szomszédos béta-sejtek inzulinelválasztására is, így eredményezve csökkent inzulintermelést [11].…”
Section: áBraunclassified